SISTEM PAKAR DIAGNOSA DEPRESI MAHASISWA TINGKAT AKHIR MENGGUNAKAN METODE CERTAINTY FACTOR - Rohani Maliyah; Ghufron Zaida Muflih (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Final-year students are vulnerable to mental health issues, particularly depression, due to various complex problems such as academic demands, life transitions after graduation, social isolation, and economic factors. However, the lack of counseling services on campus poses a barrier to the early diagnosis of depression. This study aims to design and develop a web-based expert system using the Certainty Factor method to diagnose depression levels in final-year students from the 2018 to 2020 cohorts at Ma’arif Nahdlatul Ulama University of Kebumen. The research applies a Research and Development (R&D) approach, utilizing the Certainty Factor as the basis for the decision-making system. Symptom data were collected through expert interviews and literature review, then implemented into a web-based expert system built using the PHP programming language and CodeIgniter framework. The system was tested on 40 students using stratified random sampling. The test results showed that the system achieved an accuracy rate of 100% compared to expert diagnoses. User evaluation yielded a System Usability Scale (SUS) score of 82.67% (Excellent category) and a Likert scale assessment result of 83.02% (Very Good category). Based on these results, the developed expert system is considered feasible to be used as an early detection tool for depression in final-year students and has the potential to support preventive efforts and mental health assistance services within the campus environment. Keyword: Certainty Factor, Depression, Expert System, Final-Year Students, Mental Health. Abstrak: Mahasiswa tingkat akhir rentan mengalami gangguan kesehatan mental khususnya depresi, karena menghadapi masalah yang cukup kompleks, diantaranya tuntutan akademik, transisi kehidupan setelah lulus, isolasi sosial dan faktor ekonomi. Namun, dengan tidak adanya layanan konseling bagi mahasiswa menyebabkan hambatan dalam proses diagnosa gangguan depresi. Penelitian ini bertujuan untuk merancang dan membangun sistem pakar berbasis web menggunakan metode Certainty Factor guna mendiagnosa tingkat depresi pada mahasiswa tingkat akhir angkatan 2018 hingga 2020 di Universitas Ma’arif Nahdlatul Ulama Kebumen. Penelitian ini menggunakan pendekatan Research and Development (R&D) dengan metode Certainty Factor sebagai dasar sistem pengambilan keputusan. Data gejala diperoleh melalui wawancara pakar dan studi literatur, kemudian diterapkan ke dalam sistem pakar berbasis web yang dibangun dengan bahasa pemrograman PHP menggunakan framework CodeIgniter dan diuji kepada 40 mahasiswa dengan teknik stratified random sampling. Hasil pengujian terhadap 40 mahasiswa menunjukkan sistem memiliki tingkat akurasi sebesar 100% terhadap hasil diagnosa pakar. Penilaian pengguna terhadap sistem dengan skor System Usability Scale (SUS) sebesar 82.67% (kategori Excellent), dan penilaian skala likert sebesar 83.02% (kategori Sangat Baik). Berdasarkan hasil tersebut, sistem pakar yang dibangun dinyatakan layak digunakan sebagai alat bantu deteksi dini gangguan depresi pada mahasiswa tingkat akhir, serta berpotensi mendukung upaya preventif dan layanan pendampingan kesehatan mental di lingkungan kampus. Kata kunci: Certainty Factor, Depresi, Kesehatan Mental, Mahasiswa Tingkat Akhir, Sistem Pakar